Pengaruh Kedisiplinan Terhadap Prestasi Belajar Bahasa Indonesia Siswa Kleas XII SMA Gita Kirrti 1 Jakarta Tahun Ajaran 2020/2021 - Sri Purni Hernawati (Peneliti.net, 2022)
In this research, there are two formulations, namely: Is there a relationship between discipline and students' learning achievement in Indonesian, and the second is how to instill discipline in students. The subjects of this study were students of class XII SMA GITA KIRRTI 1 Jakarta. The research sample was taken by random sampling technique, by using this technique the sample obtained was class XII, which consisted of 36 students. Data related to student discipline, researchers obtained it by distributing questionnaires. In terms of teaching and learning achievement in Indonesian, the writer takes the student's Indonesian language report card score. In this study, the method used to analyze the data is to use the product moment correlation formula with rough numbers. However, before the analysis was carried out, the previous questionnaire was tested on 26 students. The test trial was carried out using the product moment correlation formula for crude numbers, while for the reliability test the authors used two formulas, namely the product moment correlation formula for crude numbers and the second was the Spearmen Brown formula. From this test, the correlation number for the validity test is 0.51 and for the test reliability test the number obtained is 0.75. From the results of the research or analysis, the following conclusions are obtained: First: there is a positive relationship between discipline and Indonesian language learning achievement, with a correlation number of 0.6. Second: to instill a disciplined attitude by means of inner control techniques. External control techniques, cooperative control techniques, authoritarian power, liberal freedom and freedom of direction.